Preparation of drug carriers from glycosides and polymer: determine the encapsulation efficiency - Muhamad Kamil, Muhammad Khairi (2017)
Glycosides-polymer as drug carrier is used widely in pharmaceutical industry because of its pharmacological action and therapeutic effect. The drug carrier was formulated using thin film approach and the properties of the vesicle which the surface charge, size and encapsulation efficiency was studied using dynamic light scattering and fluorescence spectroscopy. Glucoside and Galactoside vesicles is formulated with the volume ratio of 1:0.4 to DCP with the effect of the presence of cholesterol to the vesicle stability and encapsulation efficiency of drug methylene blue (MB) was determined. The findings show the presence of cholesterol in the glucoside vesicle produce the highest encapsulation efficiency at 1.73% and the lowest at 1.14% for galactoside vesicle with the cholesterol absent. The loading efficiency is find to be low for all formulation at no more than 3.7%.